2002
DOI: 10.1002/cne.10473
|View full text |Cite
|
Sign up to set email alerts
|

Calbindin and calretinin immunoreactivities identify different types of neurons in the adult lamprey spinal cord

Abstract: The central pattern generator for locomotion in vertebrates is composed of different spinal neuronal populations that generate locomotor movement. In the lamprey spinal cord, several classes of interneurons have been identified based on morphologic and physiological criteria and integrated in the spinal cord circuits implicated in the generation of locomotion. However, the lack of histochemical markers for most of the interneurons makes it difficult to study whole populations along the spinal cord. We have inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 74 publications
3
28
0
Order By: Relevance
“…The CBir and CRir cell populations are more numerous in Xenopus [Morona et al, 2005[Morona et al, , 2006b]. Apart from lampreys [Megías et al, 2003], comparable cells have not been reported in the spinal cord of any other group of fishes, and in terms of location, morphology, and calcium-binding protein content, the cells detected in the ventral columns of lungfishes are very similar to those of tetrapods.…”
Section: Ventral Spinal Cordmentioning
confidence: 49%
See 3 more Smart Citations
“…The CBir and CRir cell populations are more numerous in Xenopus [Morona et al, 2005[Morona et al, , 2006b]. Apart from lampreys [Megías et al, 2003], comparable cells have not been reported in the spinal cord of any other group of fishes, and in terms of location, morphology, and calcium-binding protein content, the cells detected in the ventral columns of lungfishes are very similar to those of tetrapods.…”
Section: Ventral Spinal Cordmentioning
confidence: 49%
“…The actual proteins CB and CR have not been isolated in lungfishes, but the Western blot analysis we performed and previously published data suggest that these proteins are conserved in evolution [Wassermann and Taylor, 1966;Parmentier et al, 1987;Denizot et al, 1988] and that the use of antibodies against mammalian or avian proteins is therefore a valuable tool for identifying CBir and CRir structures in the nervous system of a wide variety of vertebrates [Martínez-Guijarro and Freund, 1992;Guirado et al, 1999;Pritz and Siadati, 1999;Cuenca et al, 2000;Dávila et al, 2000;Hackney et al, 2003;Megías et al, 2003;Bennis et al, 2005;González, 2008, 2009]. Furthermore, the present results show that the antibodies used in our analysis of the spinal cord of P. dolloi and N. forsteri yield specific immunostaining and that the simultaneous double-labeling experiments corroborate the lack of cross-reactivity in the case of lungfishes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At least in the short term, the endogenous buffering allows motoneurons to rapidly recover from Ca 2ϩ transients at a low energy cost (Palecek et al 1999). Recent evidence shows that lamprey spinal cord putative CPG neurons and motoneurons are indeed rich in Ca 2ϩ buffering molecules like calbindin and calretinin (Megias et al 2003).…”
Section: Imaging Ca 2ϩ With Low Affinity Dyesmentioning
confidence: 99%